Longitudinal changes and correlations of bioimpedance and anthropometric measurements in pregnancy: Simple possible bed-side tools to assess pregnancy evolution. (2nd December 2017) - Piuri, Gabriele; Ferrazzi, Enrico; Bulfoni, Camilla; Mastricci, Luciana; Di Martino, Daniela; Speciani, Attilio Francesco
Abstract: Purpose: The aim of this study was to assess longitudinal changes of bioimpedance analysis compared with anthropometric measurements in low-risk pregnant woman recruited in the first trimester and to observe possible differences in these indices in women who developed high-risk pregnancies. Materials and methods: Bioimpedance indices for the three trimesters of pregnancies were calculated separately for uneventful pregnancies delivered of newborns > the 10th centile. These findings were compared with anthropometric measurements. Data of women who developed hypertensive disorders of pregnancy (HDP) or delivered SGA newborns were calculated and compared. Results: Significantly longitudinal increases were observed in these pregnancies for total body water (TBW), free fat mass, fat mass, and extra-cellular water. These increases were paralleled body mass index (BMI), skinfolds, and waist measurements. The correlations between these two sets of findings were poor. Women who developed HDP with AGA fetuses showed significantly different bioimpedance from normal cases. TBW indices were highly significantly different since the first trimester. In pregnancies delivered of SGA newborns, these indices were opposite of the values observed in patients with HDP-AGA, TBW in these patients was significantly reduced compared with normal pregnancies. Conclusions: The bioelectrical impedance is a fast, simple, noninvasive way to assess the TBW content in pregnancy. Our findings are in agreement with the hypothesis that bioimpedance might help to identify early in gestation patients at risk of developing different clinical phenotypes of hypertensive disease of pregnancy and SGA fetuses.